If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + x = 4x + -7 Combine like terms: 5x + x = 6x 6x = 4x + -7 Reorder the terms: 6x = -7 + 4x Solving 6x = -7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6x + -4x = -7 + 4x + -4x Combine like terms: 6x + -4x = 2x 2x = -7 + 4x + -4x Combine like terms: 4x + -4x = 0 2x = -7 + 0 2x = -7 Divide each side by '2'. x = -3.5 Simplifying x = -3.5
| -12+7x^2=0 | | 14a-13=11a+2 | | 10x-20=-20x | | 20a+17=13a-18 | | -5(t-9)= | | -3/1.75x=19 | | w-3=4w | | 21a+6=17a+34 | | -7x-3=-45-x | | 5x-6.4=3x+2.6 | | 11cos(0)+7=0 | | 3s-2s= | | 7x-20y=-5+6y | | 6x+28=4x-16 | | 2x+(3x+5)=180 | | 6x+34=4x | | G(n)=4x+9 | | x^2+20=-2x | | 5y-8y+15=16y+5y | | 2x+6x=7x-x | | 5x^2-7x-50=0 | | -(4x-13)+2(4x+7)= | | 3xy(1+y+2xy)=0 | | Y=5.5+15x | | G(10)=4x+9 | | y/5=80 | | 64-x^4=0 | | 20x+6x-10x=15x+10x+900 | | 6(6h)= | | log7(4^3/4a-8) | | 40-(3c+4)=4c+20c | | -3+x=-4x+52 |